Perceptions of difficulties faced by first-year medical students while learning Physiology at a single Government institute in Kolkata, India - Sanhita Mukherjee; Diptakanti Mukhopadhyay (Al Ameen Medical College, 2019)
Introduction: This study investigated medical students' perception of learning difficulties in Physiology during their first year of study and their study habits to overcome these problems. Method: A total of 200 1st year medical students of a Government Medical College in West Bengal, India were surveyed by a pre-validated semi-structured questionnaire that was provided to the 2017-18 batch. Result: Among 147 respondents 74 were males and 73 were females. A majority of students considered less time and vast syllabus was the greatest difficulty faced by them in learning Physiology at 1st year (Score 4.7 out of 7 in male and Score 4.3 out of 7 in females.). Stress, anxiety during course was ranked second. 41.89% male and 46.57% female students agreed that following the instructor and taking class notes simultaneously at Physiology Lecture class was the major problem faced by them at lecture classes. Less hands-on activity was pointed out as the major problem at Physiology practical class. Majority of students (93.24% male students and 91.78% female) reported that they take help of different networking sites to improve their knowledge. Conclusion: Students' perception of difficulties in learning Physiology at their first year pointed out the need of modification of pre-convinced notion of teaching-learning principles. Curriculum encouraging self-directed learning, andragogic approach, formative assessment and constructive feedback to the students are the need of the day. Faculty members of medical colleges should update themselves accordingly and should modify their teaching mode in more learner-centric pattern.